Protective role of endorepellin in renal developmental programming - Tang, Xiaoshan; Sun, Manqing; Shen, Qian; Rao, Jia; Yang, Xue; Fang, Ye; Xiang, Tianchao; Xue, Shanshan; Sun, Lei; Xu, Hong (Frontiers in Cell and Developmental Biology, 2022)
Adverse intrauterine and early postnatal environment cause reduced nephron endowment and subsequent hypertension, chronic kidney disease (CKD). Exploring modifiable approaches is particularly important to alleviate the global burden of CKD. Enhanced glomerular progenitor cell apoptosis is a major contributor to renal developmental programming. The differentially expressed protein perlecan, which we previously identified using proteomics, is an important extracellular matrix glycoprotein, and its domain V (endorepellin) can inhibit apoptosis through a paracrine form. In explanted mice embryonic metanephros, we found that endorepellin can rescue glomeruli-deficit phenotype resulting from malnutrition, and this protective effect was also verified in vivo using a renal developmental programming model which was given a low-protein diet during pregnancy. We further demonstrated that endorepellin significantly inhibited glomerular progenitor cell apoptosis which activates ERK1/2 phosphorylation. Our results show that endorepellin rescues the nephron number reduction in renal developmental programming, possibly through the inhibition of progenitor cell apoptosis via the ERK1/2 pathway.